Fabrication and Characterisation of 3D Diamond Pixel Detectors With Timing Capabilities - Anderlini, Lucio; Bellini, Marco; Bizzeti, Andrea; Cardini, Alessandro; Ciaranfi, Roberto; Corsi, Chiara; Garau, Michela; Lai, Adriano; Lagomarsino, Stefano; Lampis, Andrea; Loi, Angelo; Lucarelli, Chiara; et al. (Frontiers in Physics, 2020)
Diamond sensors provide a promising radiation hard solution to the challenges posed by the future experiments at hadron machines. A 3D geometry with thin columnar resistive electrodes orthogonal to the diamond surface, obtained by laser nanofabrication, is expected to provide significantly better time resolution with respect to the extensively studied planar diamond sensors. We report on the development, production and characterisation of innovative 3D diamond sensors achieving 30% improvement in both space and time resolution with respect to sensors from the previous generation. This is the first complete characterisation of the time resolution of 3D diamond sensors and combines results from tests with laser, beta rays and high energy particle beams. Plans and strategies for further improvement in the fabrication technology and readout systems are also discussed.